Transformation of Islamic Education Management Through the Impactful Campus Program (Analytical Study of the Policy of the Ministry of Higher Education, Science, and Technology) - Sulaeman (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the transformation of Islamic education management through the Kampus Berdampak (Impactful Campus) policy launched by the Ministry of Higher Education, Science, and Technology. The research employs a literature review approach, drawing primarily from scholarly journal articles published within the last five years. The findings indicate that this policy has driven significant changes in the organizational structure of Islamic higher education institutions, particularly through the establishment of community service units and the integration of service-learning activities into the curriculum via the Merdeka Belajar Kampus Merdeka (MBKM) framework. Additionally, there has been an improvement in students’ soft skills development, a digital transformation in program implementation, and a strengthening of institutional reputation in the public eye. However, challenges related to resources and program sustainability remain and require cross-sector collaboration to address. The study concludes that Kampus Berdampak functions not only as a tool for community service but also as a managerial strategy to enhance the social, academic, and institutional roles of Islamic higher education in the modern era.